Role of Direct vs. Indirect Pathways from the Motor Cortex to Spinal Motoneurons in the Control of Hand Dexterity - Isa, Tadashi; Kinoshita, Masaharu; Nishimura, Yukio (Frontiers in Neurology, 2013)
Evolutionally, development of the direct connection from the motor cortex to spinal motoneurons (corticomotoneuronal (CM) pathway) parallels the ability of hand dexterity. Damage to the corticofugal fibers in higher primates resulted in deficit of fractionated digit movements. Based on such observations, it was generally believed that the CM pathway plays a critical role in the control of hand dexterity. On the other hand, a number of “phylogenetically older” indirect pathways from the motor cortex to motoneurons still exist in primates. The indirect pathways are mediated by intercalated neurons such as segmental interneurons (sINs), propriospinal neurons (PNs) reticulospinal neurons (RSNs) or rubrospinal neurons (RuSNs). However, their contribution to hand dexterity remains elusive. Lesion of the brainstem pyramid sparing the transmission through the RuSNs and RSNs, resulted in permanent deficit of fractionated digit movements in macaque monkeys. On the other hand, in our recent study, after lesion of the dorsolateral funiculus (DLF) at the C5 segment, which removed the CM pathway and the transmission through sINs and RuSNs but spared the processing through the PNs and RSNs, fractionated digit movements recovered within several weeks. These results suggest that the PNs can be involved in the recovery of fractionated digit movements, but the RSNs and RuSNs have less capacity in this regard. However, on closer inspection, it was found that the activation pattern of hand and arm muscles considerably changed after the C5 lesion, suggesting limitation of PNs for the compensation of hand dexterity. Altogether, it is suggested that PNs, RSNs RuSNs and the CM pathway (plus sINs) make a different contribution to the hand dexterity and appearance of motor deficit of the hand dexterity caused by damage to the corticofugal fibers and potential of recovery varies depending on the rostrocaudal level of the lesion.